Evaluation of cytokine responses against novel Mtb antigens as diagnostic markers for TB disease. Issue 3 (September 2016) - ,; Walzl, Gerhard; Chegou, Novel N.; Kriel, Magdalena; van der Spuy, Gian; Loxton, Andre G.; Stanley, Kim; Malherbe, Stephanus; Mcanda, Shirley; Kriel, Belinda; Phalane, Khutso G.; Essone, Paulin; et al.
Summary: Objective: We investigated the accuracy of host markers detected in Mtb antigen-stimulated whole blood culture supernatant in the diagnosis of TB. Methods: Prospectively, blood from 322 individuals with presumed TB disease from six African sites was stimulated with four different Mtb antigens (Rv0081, Rv1284, ESAT-6/CFP-10, and Rv2034) in a 24 h whole blood stimulation assay (WBA). The concentrations of 42 host markers in the supernatants were measured using the Luminex multiplex platform. Diagnostic biosignatures were investigated through the use of multivariate analysis techniques. Results: 17% of the participants were HIV infected, 106 had active TB disease and in 216 TB was excluded. Unstimulated concentrations of CRP, SAA, ferritin and IP-10 had better discriminating ability than markers from stimulated samples. Accuracy of marker combinations by general discriminant analysis (GDA) identified a six analyte model with 77% accuracy for TB cases and 84% for non TB cases, with a better performance in HIV uninfected patients. Conclusions: A biosignature of 6 cytokines obtained after stimulation with four Mtb antigens has moderate potential as a diagnostic tool for pulmonary TB disease individuals and stimulated marker expression had no added value to unstimulated marker performance. Highlights: We evaluated the utility of host markers elicited after overnight stimulation of whole blood with Mtb antigens. We identified a six analyte biosignature that showed promise in the diagnosis of active TB. The identified host markers may be useful in improving the sensitivity of immunodiagnostic assays for TB disease. Stimulation with Mtb antigens may not add value to unstimulated marker levels in the diagnosis of TB disease.